Pentingnya Sarana dan Prasarana di Sekolah terhadap Mutu Pendidikan - Sanesa Tri Manza; Yullys Helsa (STIKes Ibnu Sina Ajibarang, 2025)
This article seeks to determine the significance of facilities and infrastructure in relation to educational quality. The research employs a descriptive qualitative method, utilizing the Systematic Literature Review (SLR) approach, where the researchers examine and evaluate various sources, including journals, books, and other relevant materials connected to the topic under consideration. The findings of this research reveal that the presence of facilities and infrastructure is crucial in the educational process; from this process emerges a high-quality education, and such quality education subsequently influences the advancement of educational standards. The study's results emphasize that the availability of facilities and infrastructure plays a vital role in the learning experience, leading to the establishment of a quality educational process, which, in turn, impacts the enhancement of educational quality.